The effect of vibroacoustic therapy on the structural integrity of erythrocytes and platelets in patients with acute exogenous poisoning - M. S. Makarov; Yu. S. Goldfarb; A. V. Badalyan; A. Yu. Simonova; M. M. Potskhveriya (Трансплантология (Москва))
Background. Vibroacoustic therapy is used as a non-drug method of correcting respiratory disorders in various diseases, including acute poisoning. The effect of vibroacoustic therapy on blood cells currently remains unexplored.Objective. To evaluate the impact of vibroacoustic therapy on the morphofunctional rate of erythrocytes and platelets in patients with acute poisoning in patients with acute poisoning.Material and methods. Thirty eight patients with complicated acute poisoning transferred to the Toxicology Department of the N.V. Sklifosovsky Research Institute for Emergency Medicine were examined. In 19 patients, along with the standard therapy, a vibroacoustic therapy was performed using a VibroLUNG device (the main study group); the other 19 patients received only standard therapy (the comparison group). Vibroacoustic therapy began on the 2nd day after the patient admission to the Toxicology Department. The course of vibroacoustic therapy consisted of 2–9 procedures. Morphofunctional analysis of erythrocytes and platelets in all cases was performed before the start of the vibroacoustic therapy (before treatment) and before discharge from the hospital (1–2 days after completing the vibroacoustic therapy course).Results. In both groups, before treatment, we noted normal morphofunctional rate of erythrocytes and normal level of platelets with granules in the circulating blood. The level of severely damaged or altered platelets was only slightly higher than normal and did not differ between the groups. Meanwhile, in 50% of patients, platelets had a tendency to spontaneous activation and hyperactivation. Before discharge, the morph functional parameters of erythrocytes and platelets did not significantly change in both groups, while treatment with vibroacoustic therapy allowed to eliminate or reduce spontaneous platelet activation in 7 of 9 patients in the main study group. In the comparison group spontaneous platelet activation was absent in only 3 of 10 patients. In parallel, the time till pneumonia resolution turned statistically significantly reduced, by 1.5 times.Conclusions. In acute exogenous poisoning with complicated course, the risk of spontaneous platelet activation and hyperactivation increases. Vibroacoustic therapy does not violate the structural integrity of circulating erythrocytes and platelets. Vibroacoustic therapy, using the VibroLUNG device, reduces the tendency of platelets to spontaneous activation and hyperactivation, reduces the time for resolving pneumonia.